2019
DOI: 10.1016/s0140-6736(19)31281-4
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and cost-effectiveness of total versus partial knee replacement in patients with medial compartment osteoarthritis (TOPKAT): 5-year outcomes of a randomised controlled trial

Abstract: Background Late-stage isolated medial knee osteoarthritis can be treated with total knee replacement (TKR) or partial knee replacement (PKR). There is high variation in treatment choice and little robust evidence to guide selection. The Total or Partial Knee Arthroplasty Trial (TOPKAT) therefore aims to assess the clinical effectiveness and costeffectiveness of TKR versus PKR in patients with medial compartment osteoarthritis of the knee, and this represents an analysis of the main endpoints at 5 years. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
159
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(177 citation statements)
references
References 33 publications
15
159
2
1
Order By: Relevance
“…Furthermore, the recently published 5 year results of the Total Or Partial Knee Arthroplasty Trial (TOPKAT), a pragmatic randomised controlled trial (RCT) of over 500 patients, at 27 UK sites with This work was completed at the Nuffield Department of Orthopaedics, Rheumatology and Musculoskeletal Sciences (NDORMS), University of Oxford. 68 surgeons, has shown equivalent revision rates with TKR and UKR [1].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, the recently published 5 year results of the Total Or Partial Knee Arthroplasty Trial (TOPKAT), a pragmatic randomised controlled trial (RCT) of over 500 patients, at 27 UK sites with This work was completed at the Nuffield Department of Orthopaedics, Rheumatology and Musculoskeletal Sciences (NDORMS), University of Oxford. 68 surgeons, has shown equivalent revision rates with TKR and UKR [1].…”
Section: Introductionmentioning
confidence: 96%
“…has only found a small statistical functional difference in favour of UKA which questions the clinical relevance and continues the quest to determine if a skeleton sparing procedure with higher revision is worthwhile [2]. The clinical question which continues to be unanswered is the patientcentred complaint of gait impairment: which procedure is more likely to restore normal function?…”
Section: Introductionmentioning
confidence: 99%
“…Also, a lower risk of complications has been reported for PKR (Liddle et al 2014a, Beard et al 2019). Furthermore, a recent randomized trial demonstrated similar Oxford Knee Scores, a higher perceived knee improvement, higher willingness to undergo the operation again, and better cost-effectiveness after PKR compared with TKR at 5 years' follow-up (Beard et al 2019). Nevertheless, since its introduction, the PKR has been a topic of debate due to the diversity in reported long-term survival rates.…”
mentioning
confidence: 97%